Carbon trading : a critical conversation on climate change, privatisation and power (2006)
Makes the case that carbon trading slows the social and technological change needed to cope with global warming by unnecessarily prolonging the world's dependence on oil, coal and gas. Argues that the neoliberal approach to the crisis, promoted by the US and enshrined in the Kyoto Protocol and the EU Emissions Trading Scheme, is failing.
Keywords: EMISSION CONTROL